Recharge seasonality based on stable isotopes: Nongrowing season bias altered by irrigation in Nebraska - Cherry, Mikaela; Gilmore, Troy; Mittelstet, Aaron; Gastmans, Didier [UNESP]; Santos, Vinicius [UNESP]; Gates, John B. (Wiley, 2020)
The sustainability of groundwater resources for agricultural and domestic use is dependent on both the groundwater recharge rate and the groundwater quality. The main purpose of this study was to improve the understanding of the timing, or seasonality, of groundwater recharge through the use of stable isotopes. Based on 768 groundwater samples collected from aquifers underlying natural resources districts in Nebraska, the isotopic composition of groundwater (δ2H and δ18O) was compared with that of precipitation by (a) mapping the isotopic composition of groundwater samples and (b) mapping a seasonality index for groundwater. Results suggest that for the majority of the state, groundwater recharge has a nongrowing season signature (October–April). However, the isotopic composition of groundwater suggests that in some intensively irrigated areas, human intervention in the water cycle has shifted the recharge signature towards the growing season. In other areas, a different human intervention (diversion of Platte River water for irrigation) has likely produced an apparent but possibly misleading nongrowing season recharge signal because the Platte River water differs isotopically from local precipitation. These results highlight the need for local information even when interpreting isotopic data over larger regions. Understanding the seasonality of recharge can provide insight into the optimal times to apply fertilizer, specifically in highly conductive soils with high leaching potential. In areas with high groundwater nitrate concentrations, this information is valuable for protecting the groundwater from further degradation. Although previous studies have framed nongrowing season recharge within the context of future climate change, this study also illustrates the importance of understanding how historical human intervention in the water cycle has affected groundwater recharge seasonality and subsequent implications for groundwater recharge and quality.
Keywords: groundwater; High Plains aquifer; isoscapes; recharge; stable isotopes